Removal of Brilliant Red from Aqueous Solutions by Adsorption on Fish Scales - Begum, Hosne Ara; Kabir, Md. Humayun (Dhaka University Journal of Science, 2013)
Removal of brilliant red (C. I. Reactive Red 2) from aqueous solutions by adsorption on fish scales of Labeo rohita was investigated. Batch adsorption experiments were carried out under different experimental conditions such as contact time, initial concentration of dye solutions, temperature and pH of the solution. The optimum pH for the adsorption experiment was found to be 7.2. The equilibrium time for the adsorption of brilliant red (BR) on fish scales was estimated and found to be three hours. The amount of brilliant red adsorbed on fish scale surface decreased with increasing pH and temperature of the solution. The negative value of differential heat of adsorption suggests that the adsorption process is exothermic. Langmuir adsorption isotherm was found to fit the experimental data better than that of the Freundlich adsorption isotherm. Dhaka Univ. J. Sci. 61(1): 7-12, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15089